We do not Know Enough About Burnout Among Medical Residents in Turkey: A Rapid Review of the Literature - (:unkn) unknown (ERCIYES UNIV SCH MEDICINE, 2021)
Studies worldwide have shown that 27-75% of medical residents experience burnout syndrome. There are 26,181 residents in Turkey, and the number has been increasing. In this study, we aimed to review how much Turkish medical residents are represented in the existing literature on burnout syndrome and uncover a possible knowledge gap. In this rapid review, the PubMed database was used to identify studies on burnout syndrome among Turkish medical residents up to June 2020. A search query was designed with a combination of related keywords and narrowed by city, country, and nationality. Fifteen studies were included in the review. These studies were published between 2006 and 2019. Most of them investigated residents from a single specialty (n=7), single center (n=7), or single city (n=10). Nine studies focused only on residents. The minimum, maximum, and median numbers of residents were 11, 270, and 74, respectively. The findings of this review indicate the literature gap on burnout syndrome in medical residents in Turkey. Few studies have addressed this problem, and their findings are insufficient to represent the status of the residents. The authors encourage the scientific community to conduct various studies with rigorous methodologies.
Keywords: Burnout; medical resident; mental health; medical education; health care management